The effect of an inflammatory bowel disease nurse position on service delivery. (1st May 2014) - Leach, Peta; De Silva, Mahinda; Mountifield, Reme; Edwards, Sam; Chitti, Laurie; Fraser, Robert J.L.; Bampton, Peter
Abstract: Inflammatory bowel disease (IBD) management is increasingly concentrated in units with expertise in the condition leading to substantial improvement in outcomes. Such units often employ nurses with a specialised interest in IBD with enhancements in care reflecting in part the promotion of more efficient use of medical and hospital services by this role. However, the relative contributions of nurse specialist input, and the effect of medical staff with a sub-speciality interest in IBD are unclear although this has major implications for funding. Determining the value of IBD nurses by assessing the direct impact of an IBD nurse on reducing admissions and outpatient attendances has immediate cost benefits, but the long-term sustainability of these savings has not been previously investigated. We therefore assessed the effect of an IBD nurse on patient outcomes in a tertiary hospital IBD Unit where the position has been established for 8 years by measuring the number of occasions of service (OOS) and outcomes of all interactions between the nurse and patients in a tertiary hospital IBD Unit over a 12-month period. There were 4920 OOS recorded involving 566 patients. IBD nurse intervention led to avoidance of 27 hospital admissions (representing a saving of 171 occupied bed days), 32 Emergency Department presentations and 163 outpatient reviews. After deducting salary and on-costs related to the IBD nurse there was a net direct saving to the hospital of AUD 136, 535. IBD nurse positions provide sustained direct cost reductions to health services via reducing hospital attendances. This is additional to benefits that accrue through better patient knowledge, earlier presentation and increased compliance.